Peningkatan Pendapatan Masyarakat Meruya Melalui Afiliasi Marketing Pada Masa Pandemic Covid 19 - Lutfi Alhazami (JPM: Jurnal Pengabdian Masyarakat, 2020)
Covid-19 pandemic has changed people’s lives. Changes that occur, such as the world’s focus on health, the shift from face to face to online. Pandemic have a negative impact on people’s economic activities. Many policies have been carried out by the government in dealing with Covid-19, ranging from methods of finding people affected by the virus, social distancing, closing markets and offices. The closure of these markets and offices had an impact on the declined of community’s economic. People lost their jobs and income. In Dealing with decline in income, a community service webinar was conducted in The Meruya area by informing about affiliate marketing. This Activity aims to get passive income during pandemic Covid-19.